2022
DOI: 10.1128/spectrum.00746-22
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Metagenomic Next-Generation Sequencing for Etiological Diagnosis of Patients with Sepsis in Intensive Care Units

Abstract: Delays in effective antimicrobial therapy have resulted in decreased survival rates among patients with sepsis. However, current culture-based diagnostic methods have low sensitivity because of concurrent antibiotic exposure and fastidious and atypical causative organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
1
12
2
Order By: Relevance
“…11.11%), and the proportions of 1-3 and 4-6 pathogens detected were 72.22% and 11.11%, respectively. It was reported that the positive rate of mNGS test in blood samples of adult patients with sepsis was 62.0% ( Chien et al., 2022 ), while a higher positive rate (83.33%) of children with sepsis was observed in this study. However, no mNGS related studies of pleural or peritoneal effusions have been reported so far.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…11.11%), and the proportions of 1-3 and 4-6 pathogens detected were 72.22% and 11.11%, respectively. It was reported that the positive rate of mNGS test in blood samples of adult patients with sepsis was 62.0% ( Chien et al., 2022 ), while a higher positive rate (83.33%) of children with sepsis was observed in this study. However, no mNGS related studies of pleural or peritoneal effusions have been reported so far.…”
Section: Discussioncontrasting
confidence: 50%
“…To improve the pathogen positive rate and pathogen diagnosis accuracy, clinicians can collect samples from multiple suspected infected sites for mNGS pathogen screening ( Chien et al., 2022 ). As one of the most common sample types, blood has the easiest access for mNGS testing and is the most important sample type for joint analysis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic treatments affect the pathogens in bloodstream infection, making it tough to achieve the clinical examination. By detecting the blood samples of patients with sepsis in intensive care units, the usage of mNGS considerably improved the number of fungi ( p = 0.012) compared to conventional culture [ 79 ]. Moreover, using ITS sequencing for allogeneic hematopoietic cell transplantation (alloHCT), researchers found that the load of C. albicans was significantly high in some blood samples [ 80 ].…”
Section: Ngs and Fungal Infection In Different Organsmentioning
confidence: 99%
“…These patients are at higher risk for infections by opportunistic pathogens and thus may particularly benefit from early, reliable identification of the causative pathogen. NGS can identify a wide variety of pathogens (bacteria, fungi and viruses) within a single sample, including pathogens that are difficult to cultivate or are slow-growing such as atypical mycobacteria, which are rarely examined [6]. However, 7 patients are a very small number and larger multicenter cohorts are needed to make valid statements.…”
Section: Discussionmentioning
confidence: 99%